Subclinical Atherosclerosis in Young Adult Population with First Degree Relatives of Type 2 Diabetes Mellitus - Muhammad Syah Abdaly; Mohamad Syahrir Azizi; Ika Prasetya Wijaya; Pringgodigdo Nugroho; Dyah Purnamasari (Acta Medica Indonesiana)
Cardiovascular disease (CVD) remain a leading cause of death globally. The concept of acute myocardial infarction in young adults was uncommon. Atherosclerosis is the leading cause of CVD, including myocardial infarction, stroke, heart failure and peripheral artery disease. This condition is initiated early in childhood and progressive in nature. CVD risk factors includes hypertension, dyslipidemia and obesity play a role in the development of atherosclerosis and  components in insulin resistance syndrome.